Assessment of Clinical Course and Treatment Responses in Our Patients with Immune Thrombocytopenia - Oral, Kübra; Aksöz, Zekeriya; Uysal, Ayşe; Gözel, Nevzat (DAHİLİYE UZMANLARI DERNEĞİ, 2026)
Objective: Immune thrombocytopenia (ITP) is an acquired thrombocytopenia resulting from autoantibodies against platelet antigens. In this study, we aimed to analyze demographics, clinical characteristics, and treatment responses in our patients with chronic ITP on follow-up. Methods: This is a retrospective study. Data, including sociodemographic and laboratory data, treatments received, and response rates, were retrieved from patients’ electronic health records or paper charts. Results: A total of 92 patients were included in the study, and 62 (67.4%) were females. The median age of study patients was 40 years (range: 18-81years). During follow-up, evidence of bleeding was detected in 35 patients. Gastrointestinal bleeding was observed in four patients, and intracranial bleeding in three patients. No statistically significant difference was found in response rates between methylprednisolone and dexamethasone (p=0.795) in the first-line treatment and between eltrombopag and splenectomy (p=0.502) in the second-line treatment. Patients undergoing splenectomy were more likely to develop thrombosis. Conclusion: In this cohort of chronic ITP patients, the disease was more prevalent in females, with a median age of 40 years, and bleeding complications occurred in a substantial proportion of patients, including rare but serious events such as intracranial hemorrhage. No significant differences were observed in response rates between first-line treatments (methylprednisolone vs. dexamethasone) or second-line treatments (eltrombopag vs. splenectomy). However, splenectomy was associated with a higher risk of thrombosis. These findings highlight the need for individualized treatment decisions and emphasize that standardization of treatment strategies and follow-up duration is essential to better evaluate treatment responses and long-term outcomes in chronic ITP.
Keywords: Immune thrombocytopenia; Treatment; Response assessment